Analisis Kerentanan Serangan Cross Site Scripting (XSS) pada Aplikasi Smart Payment Menggunakan Framework OWASP - Imam Riadi; Rusydi Umar; Tri Lestari (UIN Sunan Kalijaga Yogyakarta, 2020)
E-commerce that is growing so rapidly can provide space for unauthorized parties in carrying out cybercrime, security anticipation is needed so that e-commerce applications can be protected from harassment or hacking attacks such as cross-site scripting (XSS), malware, exploits, and database injection. This research was conducted to determine the vulnerability of the Smart Payment application by self-test using the ZAP tool. This test is carried out to secure applications that serve as recommendations for follow-up in securing the Smart Payment application. The results of this study found vulnerabilities in the Smart Payment application. Vulnerabilities found were Information Disclosure-Suspicious Comments, X-Frame-Options Header not Set, X-Content-Type-Options Header Missing, Timestamp Disclosure-Unix, XSS Protection Not Enabled Web Browsers, and Directory Browsing. In addition to obtaining vulnerabilities from the Smart Payment application, solutions are also provided to overcome vulnerabilities in the Smart Payment application.